The 3Cs in Volunteerism: Proposing a Model of Service-Learning in Education - Edwin B. Estrera (IAFOR Journal of Education, 2024)
Curriculum strategies on social justice in education often focus on classroom management and technology integration, which may be surface-level approaches. Emerging trends include project-based learning and community partnerships for students to address real-world problems; as such, selected courses employ service-learning as a method of volunteerism. However, the participation of the students ends as soon as the course ends. Thus, this study examined the motives for volunteering and the experiences of selected high school, college, and graduate students to understand what contributes to sustained volunteerism. Seven focus group discussions among 33 key informants were conducted, and the data were analyzed using combined thematic analysis and Colaizzi's method. Following the domains of affiliation, beliefs, career development, and egoism, findings revealed that the volunteer motivations among high school students primarily relate to civics, while college students are motivated by both civics and career development. Graduate students show motivations linked to civics, career development, and competence. This study proposes the 3Cs Model of Volunteerism, which views volunteerism as a continuum rather than a one-time activity; it aims to recruit and sustain volunteers across different educational levels. By gaining a deeper understanding of student experiences in service-learning activities, educational institutions can better identify and address the needs and motivations of students, ultimately enhancing student volunteerism and community engagement necessary for promoting social justice and nation-building.